Long‐Range Fluorescence Propagation in Amyloidogenic β‐Sheet Films and Fibers. Issue 9 (8th March 2020) - Apter, Boris; Fainberg, Boris; Handelman, Amir; Lapsker, Igor; Accardo, Antonella; Diaferia, Carlo; Morelli, Giancarlo; Rosenman, Gil
Abstract: Newly developed PEGylated phenylalanine peptide derivatives (PEG‐F6) can self‐assemble to form hybrid multifunctional nanostructures of homogeneous thin polymer films and amyloid‐like fibers. Both adopt a β‐sheet architecture and acquire the unique properties of visible fluorescence (FL) found in β‐sheet amyloid fibrils also associated with neurodegenerative diseases. A new paradigm observed in PEG‐F6 amyloid‐like fibers is reported, which demonstrates unique FL and optical absorption (OA) covering the entire visible region. Despite the full overlap of the FL and OA spectra, the FL propagates for an unexpectedly large distance of hundreds of micrometers in these fibers. A new non‐waveguiding mechanism of FL light energy transfer in amyloidogenic fibers is proposed based on photon reabsorption theory. The discovered quasi‐white FL of PEG‐F6 β‐sheet amyloidogenic fibers and films consists of the newly observed green FL band along the known blue FL band. The proof‐of‐concept of long sub‐millimeter range FL propagation in specially grown amyloidogenic PEG‐F6 fiber‐photonic probes is reported. The results indicate that FL can propagate in nanoscale fibers and suggest biomedical applications for FL monitoring of disease‐related ultrathin amyloid fibrils and in integrated photonics for optogenetics. Abstract : New hybrid polymer/peptide PEGelated‐hexaphenylalanine materials self‐assemble to amyloidogenic thin films and fibers which exhibit tunable fluorescence (FL) covering entire visible spectrum. The FL propagates in b ‐sheet amyloidogenic fibers for an unexpectedly large distance of hundreds of micrometers despite of strong optical absorption. New non‐waveguiding mechanism of photon reabsorption indicates the FL propagation in nanoscale disease‐related amyloid fibrils and application in integrated photonic chips for optogenetics.